Association of anti-citrullinated protein or peptide antibodies with left ventricular structure and function in rheumatoid arthritis. (16th December 2016) - Geraldino-Pardilla, Laura; Russo, Cesare; Sokolove, Jeremy; Robinson, William H.; Zartoshti, Afshin; Van Eyk, Jenny; Fert-Bober, Justyna; Lima, Joao; Giles, Jon T.; Bathon, Joan M.
Abstract: Objective. High levels of ACPAs in RA are associated with more severe arthritis and worse prognosis. However, the role of ACPAs in mediating the increased risk of heart failure in RA remains undefined. We examined whether specific ACPAs were associated with subclinical left ventricular (LV) phenotypes that presage heart failure. Methods. Sera from RA patients without clinical cardiovascular disease were assayed for specific ACPAs using a custom Bio-Plex bead assay, and their cross-sectional associations with cardiac magnetic resonance-derived LV measures were evaluated. High ACPA level was defined as ⩾ 75th percentile. Findings were assessed in a second independent RA cohort with an expanded panel of ACPAs and LV measures assessed by 3D-echocardiography. Results. In cohort 1 (n = 76), higher levels of anti-citrullinated fibrinogen41–60 and anti-citrullinated vimentin antibodies were associated with a 10 and 6% higher adjusted mean LV mass index (LVMI), respectively, compared with lower antibody levels (P < 0.05). In contrast, higher levels of anti-citrullinated biglycan247–266 were associated with a 13% lower adjusted mean LVMI compared with lower levels (P < 0.001). In cohort 2 (n = 74), the association between ACPAs targeting citrullinated fibrinogen and citrullinated vimentin peptides or protein and LVMI was confirmed: higher anti-citrullinated fibrinogen556–575 and anti-citrullinated vimentin58–77 antibody levels were associated with a higher adjusted mean LVMI (19 and 15%, respectively; P < 0.05), but no association with biglycan was found. Conclusion. Higher levels of antibodies targeting citrullinated fibrinogen and vimentin peptides or protein were associated with a higher mean LVMI in both RA cohorts, potentially implicating autoimmune targeting of citrullinated proteins in myocardial remodelling in RA.